Outsourcing of Information Technology: An Empirical Study in the Indian Banking Industry - Mohapatra, Suryanarayan; Sahoo, Debajani; Kesharwani, Ankit (Indian Journal of Finance, 2015)
This article studied the key influencing factors that contributed to the decision of commercial banks in India to go in for information technology outsourcing. The research model considered three major drivers of outsourcing and their impact on overall organizational performance. The research approach was illustrated by discussions with senior bankers of various public and private sector commercial banks as well as vendor organizations providing outsourcing services to the banks. Factor analysis suggested that the existence of three factors - Construct Skill and Cost Savings, Technology Benefits, and Strategic Advantage - guided their outsourcing decisions. The findings of structural equation modelling suggested that technology benefits had a direct impact on strategic benefits, but did not have a direct impact on overall organizational satisfaction mediated through skill and cost benefits. In the same way, strategic benefits had an impact on organizational benefits mediated through skill and cost benefits. An important insight from this study is that managers in the banking industry do not consider that technology benefits have a direct impact on the overall organizational satisfaction. This study offers helpful information and guidance to the bank managers for taking decisions related to IT outsourcing. The present study will motivate and justify the bank managers to enforce outsourcing in their organizations.